1994
DOI: 10.1055/s-2007-1021105
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values of Isokinetic Maximum Strength, the Strength/Velocity Curve, and the Angle at Peak Torque of All Degrees of Freedom in the Shoulder

Abstract: Many acute and chronic complaints in the shoulder joint are due to a reduced active stabilization capacity. Procedures to measure isokinetic strength are used to objectify the muscle deficits and imbalances of various muscle groups. In this study, standard values and reference ranges were determined for peak torque (PT), strength/velocity curve, and range of motion (ROM) at peak torque in the shoulder in 19 untrained women and 32 men. Differentiation was made by the individual degrees of freedom of the shoulde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
1
7

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 22 publications
3
36
1
7
Order By: Relevance
“…Collectively, normal values in this and previous studies show strength development within the standard limits for the SCI population. 16 We confirmed that our 8-week training programme had positive effects on isometric strength and improved all movements tested. However, isokinetic tests showed the specificity of the resistance training programme used; that is because improvements were made in external and internal rotation for both speeds, but only at 1801 Á s À1 in adduction and internal rotation.…”
Section: Discussionsupporting
confidence: 73%
“…Collectively, normal values in this and previous studies show strength development within the standard limits for the SCI population. 16 We confirmed that our 8-week training programme had positive effects on isometric strength and improved all movements tested. However, isokinetic tests showed the specificity of the resistance training programme used; that is because improvements were made in external and internal rotation for both speeds, but only at 1801 Á s À1 in adduction and internal rotation.…”
Section: Discussionsupporting
confidence: 73%
“…13 In addition, at the shoulder, the joint angle where the peak torque is generated has been found to be difficult to reproduce between tests. 14,15 Interests of the angle subgroup agonist-antagonist torque ratios A new interpretative approach of the torque ratios between shoulder agonist and antagonist muscle groups is proposed in the current study. In addition to the F/E and Ab/Ad peak torque ratios, the F/E and Ab/Ad torque ratios were evaluated over the entire selected range of motion to refine their interpretation.…”
Section: Limits Of Agonist-antagonist Peak Torque Ratiosmentioning
confidence: 99%
“…Muscle strength can be measured during isometric, isotonic and isokinetic contractions. Peak torque is the maximum value of muscle strength [3,10]. During the design of the study, we noted that muscle strength can be measured by two different methods: using a manual muscle test or an isokinetic dynamometer.…”
mentioning
confidence: 99%